Analisis Kinerja Keuangan dengan Menggunakan Metode Financial Value Added (FVA) pada PT Semen Indonesia (Persero) Tbk Periode 2019-2024 - Renada Yustira Minangga; Afrizawati; Agung Anggoro Seto (Jurnal Inovasi Manajemen, Kewirausahaan, Bisnis dan Digital, 2025)
This study aims to assess the financial performance of PT Semen Indonesia (Persero) Tbk over the period of 2019–2024. The evaluation was conducted using the Financial Value Added (FVA) method, employing a descriptive quantitative approach. The data used in this study is secondary data, obtained from the company's financial statements through documentation methods and literature review. The analysis results show that the FVA value of the company is in a positive condition (FVA > 0), indicating efficiency in the utilization of fixed assets. A positive FVA value means that the operational net profit, plus depreciation, is able to exceed the expenses related to fixed assets, such as depreciation costs and asset management. In this case, the company provides a positive financial contribution to shareholders, even though it has not yet fully created optimal economic value. However, although the company's FVA value shows positive results, it does not fully reflect that PT Semen Indonesia has created significant economic value. This is because, despite the company's efficiency in managing fixed assets, the creation of sustainable economic value still needs to be the focus. Aspects such as increased productivity, better cost management, and income diversification need to be considered in order to generate higher added value in the long run. Overall, this study concludes that PT Semen Indonesia (Persero) Tbk has demonstrated positive financial performance related to the efficient use of fixed assets. However, the company needs to pay attention to other factors that can enhance the creation of economic value-added. With the right strategies, the company is expected to create more significant economic value and achieve financial sustainability in the long term.